(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The Paper on the representation of medical women in the late nineteenth and early twentieth century is expected to yield several significant outcomes. Firstly, it will providea deeper understanding of the historical context in which medical women operated during this period.By examining the prevailing social,cultural, and historical factors ,the paper will shed light on the attitudes ,gender norms, and challenges faced by women pursuing careers in medicine. Furthermore, the paper is anticipated to identify common representation patterns in literature, media, and public discourse regarding medical women. This analysis will reveal the presence of stereotypes, narratives of empowerment or marginalization, and the portrayal of women as trailblazers or exceptions in the field of medicine. Additionally, the paper aims to uncover the gender biases, prejudices, and challenges encountered by medical women during the late 19th and early 20th century. By exploring the barriers they faced in their professional and personal lives, the paper will contribute to a better understanding of societal expectations placed upon on women in medicine during that era.